(untitled) (El Hilo de la Fabula, 2022)
This article presents the most relevant aspects of the Greek-Spanish translation process of the dialogue Prometheus, by Lucian of Samosata (c. AD 120-180). The debates within the group, the interchange of opinions and points of view, translation criteria, and theoretical and methodological principles and decisions that converged to give its final shape to this book are also included. Lucian’s Prometheus translation was published in a bilingual version, with introduction, notes, repercussion, glossary, index of proper names and exercises, by the Faculty of Humanities and Arts of the National University of Rosario publishing house.